Building AI-powered application with .NET - Williams, Trevoir (Packt Publishing, 2025)
In this comprehensive course, you'll explore the transformative intersection of AI, machine learning, and .NET development. Starting with the foundational concepts of AI and ML, you'll gain an in-depth understanding of key topics like generative AI, neural networks, and ethical implications. With a strong theoretical base, you'll transition seamlessly into setting up your development environment and working with ML.NET. The course emphasizes hands-on learning, guiding you through creating AI-powered applications with .NET and Azure. You'll learn to train models, process data, and integrate generative AI capabilities such as language models, copilots, and advanced Azure services. Step-by-step modules will walk you through developing intelligent solutions, including text classification, sentiment analysis, and image recognition applications, all with robust tools like Azure AI Cognitive Services and OpenAI models. By the end of the course, you'll have built multiple end-to-end projects that showcase your ability to leverage AI for innovative solutions. Whether deploying smart APIs, creating chatbots, or mastering tools like Azure AI Studio and RAG, this program equips you to build smarter, scalable applications that redefine modern development.
Online resource; title from title details screen (O'Reilly, viewed January 27, 2025)
Keywords: Microsoft .NET Framework; Application program interfaces (Computer software); Application software -- Development; Artificial intelligence; Machine learning; Interfaces de programmation d'applications; Logiciels d'application; Développement; Intelligence artificielle; Apprentissage automatique; APIs (interfaces); artificial intelligence; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet